Marketing Communication Strategy for Shafira Store Surakarta Using Instagram Social Media Platform for Effective Engagement - Putri Hardani, Arlinda; Suryono, Joko (CV. Bimbingan Belajar Assyfa, 2023)
Shafira is a leading Muslim fashion brand, renowned for its stylish products geared towards both teenagers and adults. This study explores the marketing communication strategy employed by Shafira Store Surakarta on Instagram. Utilizing a qualitative descriptive approach, data were collected through observation, in-depth interviews with 10 participants, and content analysis of Shafira's Instagram posts over a six-month period. The participants included Shafira customers, marketing experts, and influencers to ensure diverse perspectives. The credibility, transferability, dependability, and confirmability of the data were rigorously tested to ensure validity. The analysis revealed that Shafira's Instagram marketing strategy effectively captures consumer attention through visually appealing advertisements that align with contemporary aesthetic trends. Collaborations with influencers possessing significant and relevant followings have proven particularly successful, leading to a 25% increase in follower count and a 35% rise in engagement rate within the observed period. Additionally, the strategic use of interactive Instagram features such as stories, polls, and live sessions has enhanced consumer interaction and brand loyalty. However, this study acknowledges certain limitations, including the exclusive focus on Instagram, which may not fully capture the broader social media landscape, and potential biases from self-reported data. The findings primarily pertain to Shafira's specific target market and may not be universally applicable to all fashion brands. Nevertheless, this research contributes to the marketing literature by providing valuable insights into how targeted and aesthetically tailored strategies on Instagram can boost brand visibility and consumer engagement. Future studies could expand by incorporating additional social media platforms and considering external factors influencing marketing strategies.